Pelatihan Konseling Kelompok Pembayangan Terbimbing Berfokus Solusi pada Guru BK SMP di Kota Batu - Ramli, M; Hidayah, Nur; Rahman, Diniy Hidayatur; Saputra, Nur Mega Aris; Hanafi, Husni (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2022)
The low group counseling skills at the Guidance and Counseling Teacher Consultation (MGBK) in Batu City is indicated by the intensity of conducting group counseling services. In fact, the more complex the problems faced by students require steps and innovations for counselors in the implementation of services. The purpose of the training is to develop the competence of counselors in understanding and applying the skills of solution-focused guided imagery group counseling. The training implementation method uses structured learning with stages of preparation, assessment, implementation, and evaluation (3PE). The results of the training showed that the trainees were enthusiastic about the implementation of the training and the evaluation of the results showed an increase in the application of solution-focused guided imagery group counseling.